Exit Consent Solicitations Post-Assenagon: A Relic of the Past? - Tsano Kanchev (UCL Journal of Law and Jurisprudence, 2020)
To download this paper, please click here. This case note considers the Assenagon judgment, which reviewed the position of exit consent solicitations in English law. Exit consent solicitation is a restructuring technique utilised in cases where a company in financial distress seeks to reorganise its debts, more specifically its bonds. In order to avoid the strenuous process of insolvency, such bond issuers put forward an exchange offer, which permits the swap of distressed bonds for newly issued ones. The exchange offer is then coupled with an exit consent, which makes it a condition of the exchange that the bondholders firstly agree to an amendment of the original terms of the defaulting bonds. Such a move allows the issuer to reorganise its financial affairs in order to keep the company afloat. Briggs J did not see the purpose of exit consents positively. He held in Assenagon that such an exchange offer coupled with exit consents was invalid by virtue of the ‘abuse principle’ as the majority, at the invitation of the issuer, took part in ‘coercing’ the minority to swap their bonds. This case note outlines the key elements of Briggs J’s ruling and discusses the future of exit consents post-Assenagon.